Research on Short Video Communication Strategy of Live-Streaming Farmers in China’s Rural Revitalization : – Take "Dongbei Yujie" on Douyin APP as an Example - Hu, Yibing; Xu, Wenjia (Transactions on Social Science, Education and Humanities Research, 2024)
With the popularization and flourishing of rural We Media, Live-streaming farmers who use short videos to sufficiently present rural customs and landscapes have emerged. While reshaping the profile of rural areas and the identity of farmers, they have also facilitated the development of "Three Rural Issues", becoming "contributing farmers" which reflect and promote the construction of rural revitalization and digital design. This article conducts a “5W” communication mode on the released account "Dongbei Yujie" which has both personal creative characteristics and huge audience groups on the mainstream short video platform - Douyin. The purpose is to explore the media content production and communication strategies of the typical Live-streaming farmers, to provide innovative dimensions for the creation of short videos on "Three Rural Issues" and to help the sustainable development of the new formats in rural revitalization.